Assessment for learning: perceptions of English and Portuguese science teacher students - Cid, Marília (2015)
Assessment and learning are understood as closely interrelated, assuming that assessment is an integral part of the learning process. Assessment for learning is seen furthermore as serving the purpose of promoting pupils’ learning. This study examines the perceptions of six science prospective teachers in England and Portugal about assessment by replying to an open self-report questionnaire, constructed for this purpose. The English students were enrolled on a postgraduate certificate in education (PGCE) course, focused on developing their teaching skills. The Portuguese students were attending a master degree in education also aiming the same goals. All the participants already had a degree on science and were in practice at schools (either basic or secondary). A qualitative analysis of students’ responses was made in order to comprehend their understanding about assessment, assessment strategies they perceive to be the most effective for learning and the relationship between learning and formative assessment. The results show that despite the difference of contexts assessment is not easy to define and raises many questions when put into practice, leading to a variety of understandings and solutions in the classroom. Nevertheless, they all tend to a summative perspective rather to a really assumed formative assumption.